Outcome of Late Presentation of Posterior Urethral Valves in a Resource-Limited Economy: Challenges in Management - Odutola Israel Odetunde; Oluwatoyin Arinola Odetunde; Adesoji Oludotun Ademuyiwa; Henrietta Uche Okafor; Uchenna Ekwochi; Jonathan Chukwuemeka Azubuike; Nene Elsie Obianyo (International Journal of Nephrology)
Delayed presentation of patients with posterior urethral valve with complications like severe urosepsis, uremia, and anemia are seen in our setting. Renal replacement therapy which should have been offered to these patients is not readily available for children in our country. The aim of this study is to determine the pattern of late presentation and outcome of management of posterior urethral valve in a resource-limited setting. A descriptive retrospective study (1997–2009) was conducted. Data including pattern of presentation, duration of symptoms, complications, and outcome of initial management were analyzed. Twenty-one patients were seen. The median age was 3 years (2 days–13 years). The mean duration of symptoms before presentation was 2.6 years. Nineteen patients (91%) presented with urosepsis while 8 patients (36%) presented with significant renal insufficiency. Laboratory findings varied from-mild-to marked elevation in serum creatinine. Radiological findings confirmed the diagnosis of posterior urethral valve. We concluded that late presentation is common in our setting. This is associated with high morbidity and mortality rates. Efforts at improving awareness and early diagnosis among the health team should be made to stem the tide.